2004
DOI: 10.1007/s00429-004-0399-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of the amygdalohypothalamic projection in the mouse embryonic forebrain

Abstract: The amygdalohypothalamic projection, a major component of the stria terminalis, is involved in the conduction of emotional and olfactory information integrated in the amygdala to the hypothalamus to elicit emotional reactions. Despite the extensive studies on functional aspects of the amygdaloid complex, developmental mechanisms of the amygdala and related structures are still poorly understood. To investigate the development of the amygdalohypothalamic projection in the mouse embryonic brain, carbocyanine dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…In agreement with this proposal, our tract-tracing experiments showed that many of the subdivisions of the chicken central extended amygdala project to the lateral hypothalamus, a feature typical of the central extended amygdala in different vertebrates (Alheid et al, 1995; Cassell et al, 1999; Aizawa et al, 2004; Moreno and González, 2006; Martínez-García et al, 2007). We discuss the evidence below, first for the lateral region encompassing subdivisions comparable to the central amygdala and intercalated amygdalar cells of mammals (Section “Lateral Region of the Central Extended Amygdala and Surrounding Areas”), and then for the medial region encompassing the BSTL (Section “Medial Part of the Central Extended Amygdala: BSTL”).…”
Section: Discussionsupporting
confidence: 84%
“…In agreement with this proposal, our tract-tracing experiments showed that many of the subdivisions of the chicken central extended amygdala project to the lateral hypothalamus, a feature typical of the central extended amygdala in different vertebrates (Alheid et al, 1995; Cassell et al, 1999; Aizawa et al, 2004; Moreno and González, 2006; Martínez-García et al, 2007). We discuss the evidence below, first for the lateral region encompassing subdivisions comparable to the central amygdala and intercalated amygdalar cells of mammals (Section “Lateral Region of the Central Extended Amygdala and Surrounding Areas”), and then for the medial region encompassing the BSTL (Section “Medial Part of the Central Extended Amygdala: BSTL”).…”
Section: Discussionsupporting
confidence: 84%
“…4c,d). These findings suggest that the trajectory labeled at E11 is the efferent trajectory originating from the Ce that we previously demonstrated by the DiI‐tracing method (Aizawa et al,2004). The trajectory labeled at E12, on the other hand, is thought to be mainly the afferent trajectory originating from the BNST, because the connection between the medial part of the Ce and the BNST has been reported to be reciprocal (Dong et al,2001a,b; Dong and Swanson,2004) and the time of neurogenesis of the BNST, especially the caudal part, is later than that of the amygdalar Ce (Bayer1987).…”
Section: Discussionsupporting
confidence: 78%
“…The sympathetic nervous system (SNS) innervates the liver and controls hepatic glucose production. Our data indicate that the amygdala may play a role in the regulation of hepatic glucose metabolism and, eventually, systemic glucose levels, directly or through other brain regions with which it has projections, such as the hypothalamus (43). Indeed, it has been shown that insulin injected in the central amygdala activates neuronal populations in regions of the hypothalamus (44) known to affect the autonomic output to the liver.…”
Section: Discussionmentioning
confidence: 80%